2022
DOI: 10.1073/pnas.2214123120
|View full text |Cite
|
Sign up to set email alerts
|

NADP(H)-dependent biocatalysis without adding NADP(H)

Abstract: Isocitrate dehydrogenase 1 (IDH1) naturally copurifies and crystallizes in a resting state with a molecule of its exchangeable cofactor, NADP + /NADPH, bound in each monomer of the homodimer. We report electrochemical studies with IDH1 that exploit this property to reveal the massive advantage of nanoconfinement to increase the efficiency of multistep enzyme-catalyzed cascade reactions. When coloaded with ferredoxin NADP + reductase in a nanoporous conducting ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 51 publications
3
21
0
Order By: Relevance
“…This current enhancement can be compared to a recent experimental work that demonstrated an enhancement factor of B25 at [NADP + ] B50 mM. 31 The results here show that the coupled current does increase with higher [NADP + ] (by 4100-1000 times compared to the uncoupled current, depending on the E2 activity), but at higher [NADP + ] (4100 mM) the contribution from the coupled current can become obscured by the bulk supply of [NADP + ], resulting in markedly smaller enhancement factors. In the context of a cofactor recycling system, there is a need to balance the requirement for higher cofactor turnover number (i.e.…”
Section: Resultsmentioning
confidence: 75%
“…This current enhancement can be compared to a recent experimental work that demonstrated an enhancement factor of B25 at [NADP + ] B50 mM. 31 The results here show that the coupled current does increase with higher [NADP + ] (by 4100-1000 times compared to the uncoupled current, depending on the E2 activity), but at higher [NADP + ] (4100 mM) the contribution from the coupled current can become obscured by the bulk supply of [NADP + ], resulting in markedly smaller enhancement factors. In the context of a cofactor recycling system, there is a need to balance the requirement for higher cofactor turnover number (i.e.…”
Section: Resultsmentioning
confidence: 75%
“…As shown in Figure A, human IDH1 copurifies with one molecule of NADP­(H) bound at each monomer active site. , The tight binding of the cofactor to a resting inactive state of the enzyme (which is not reflected in steady-state K M determinations) allows each half of the IDH1 molecule to deliver up to a 1:1 stoichiometric quantity of NADP­(H) into the pores alongside FNR, without any exogenous NADP­(H) being required. Based on a proposed model, only after Mg 2+ and isocitrate bind to the enzyme to initiate a catalytic cycle is the cofactor released for rapid recycling by a nearby FNR molecule . The loading of IDH1 with its cofactor cargo resembles advanced drug delivery mechanisms where shuttle particles carry tightly bound cargo molecules to specific locations before they are released when instructed.…”
Section: The Electrochemical Leafmentioning
confidence: 88%
“…Further experiments were carried out to address the question of whether pausing catalytic turnover results in preferential dissociation of NADP + (under an oxidizing potential) or NADPH (under a reducing potential) (Figure E,F). Chronoamperometry experiments in which the potential was periodically switched between oxidizing and reducing values revealed that the 2OG-reducing IDH1 R132H/FNR system loses activity after the first oxidative pause, whereas the isocitrate-oxidizing wild-type IDH1/FNR system is much more stable following a reductive pause . A useful analogy is found with an “electromagnetic gripper”, a machine that picks up or drops a steel load depending on the electrical command given.…”
Section: The Electrochemical Leafmentioning
confidence: 99%
See 2 more Smart Citations